Development of Desmos-Assisted Electronic Student Worksheet Based on the 5E Inquiry Learning Model to Enhance Mathematical Reasoning Skills: Supporting SDG 4 Quality Education - Rahmi; Zelhendri Zen; Jasrial; Rayendra (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop an electronic student worksheet (e-LKPD) based on the 5E Inquiry Learning model assisted by Desmos and to evaluate its validity, practicality, and effectiveness in enhancing mathematical reasoning skills (MRS) in senior high school mathematics. A Research and Development (R&D) approach using the ADDIE model was employed, implemented through a one-group pretest-posttest pre-experimental design. The e-LKPD was developed for Grade X students at SMAN 1 Pariaman on the topic of Linear Programming. Expert validation yielded an average score of 98% (highly valid) across content, language, and media aspects. Practicality testing yielded teacher response of 88.6% and student response of 97% (both highly practical). Effectiveness was evaluated via N-Gain analysis; mean pretest scores increased from 32 to 71 post-intervention, with an average N-Gain of 0.57 (medium category). The Wilcoxon signed-rank test confirmed statistically significant improvement (p ≤ 0.001). These findings indicate that the e-LKPD integrating the 5E inquiry model with Desmos technology constitutes a valid, practical, and moderately effective instructional tool for advancing mathematical reasoning skills in senior high school mathematics.